ASIAN ENGLISH LITERATURE'S MIDTERM EXAMINATION MATERNAL INSTINCT DEPICTED IN VERENATAY'S BROKEN - Indra Darmawan, Ruly (Lire Journal (Journal of Linguistics and Literature), 2018)
In this essay, I want to analyze how maternal instinct is depicted in one short story which has South East Asia as a setting of place because this maternal instinct has became one of the most debatable issues in feminist study until nowadays. The main data is a short story entitled Broken. This short story was included in anthology of Asian short stories entitled A Rainbow Feast. One thing which becomes uniqueness in Broken that picks my interest is how this novel exploits woman acts and habits in different way than any other novel. VerenaTay through this novel tells a story about one particular woman and how she treats her newborn baby. Different with other novel, Broken pictures the woman who lives in different world than us, a human. It is interesting to see how VrenaTay pictures that woman acts and somehow lives after she was dead, how a woman escapes from subversive condition and move toward dominant one by leap through the limit of life and death.